An approach to diagnosing brain death in patients undergoing extracorporeal membrane oxygenation - Altınsoy, Savaş; Baran Akkuş, İlkay; Çatalca, Sibel; Kavak Akelma, Fatma; Özhan Çaparlar, Ceyda; Ergil, Jülide (The European Research Journal, 2020)
Objectives: This study was intended to discuss the process of brain death diagnosis of patients undergoing extracorporeal membrane oxygenation (ECMO) and our approach regarding the existing literature.Methods: Demographics data (age, gender, admission diagnosis) were noted. ECMO type applied (veno-venous or veno-arterial), time of diagnosing brain death (the time from admission time till diagnosis), being a donor or not, apnea testing application, supplementary tests applied at diagnosis stage (cerebral angiography, computerized tomography angiography, electroencephalography, transcranial doppler ultrasonography), and time of cardiac death (the time elapsing from the moment of brain death diagnosis till cardiac arrest) were noted.Results: Forty-two patients data were exaimed and ECMO was applied to 8 patients, 4 of whom are female and the others are male. The average age of the patients is 61.8 ± 9.8 years. The average time elapsing from the hospitalization till brain death diagnosis was 2.5 ± 0.5 days. Apart from that, only 2 (25%) of the patients were donors.Conclusions: The use of modified apnea testing on patients undergoing ECMO could be proliferated if such tests are standardized and reliable guidelines are set. For this reason, we think that cerebral angiography should be kept in mind in addition to apnea test especially on ECMO-treated patients.